Does Anti-Gout Agent Allopurinol Affect Human Hormones Profile? - Emad F. Eskander, Ahmed A. Abd-Rabou, Hanaa H. Ahmed (Journal of Applied Pharmaceutical Science, 2013)
The main objective of the prospective study is to investigate the influence of zyloric (allopurinol) drug on the human hormones profile. Sera separated from whole blood samples were withdrawn from adult males and females to measure serum FSH, E2, LH, Prolactin, Progesterone, DHEAS, Testosterone, TSH, T3, T4, Fasting Insulin, and Cortisol. All these hormone concentrations were determined quantitatively using ELISA procedure. The current study shows significant changes within all volunteers' hormones. We concluded that the present study may be useful in drug dose optimization depending on the drug effect on each human hormone and in the addition of new medical guidelines for drug companies to avoid negative side effects that could harm the patient.
Keywords: Gout, Zyloric, Allopurinol, Human hormones profile.